2020
DOI: 10.1080/21678421.2020.1861022
|View full text |Cite
|
Sign up to set email alerts
|

Associations between autoimmune diseases and amyotrophic lateral sclerosis: a register-based study

Abstract: Objective: To assess the associations of 43 autoimmune diseases with the subsequent risk of ALS and further evaluate the contribution of familial confounding to these associations. Methods: We conducted a nationwide register-based nested case-control study including 3561 ALS patients diagnosed during 1990-2013 in Sweden and 35,610 controls that were randomly selected from the general population and individually matched to the cases on age, sex, and county of birth. To evaluate the contribution of familial fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 46 publications
(43 reference statements)
4
23
1
Order By: Relevance
“…The concurrence between ALS and MG has also been reported (3,(7)(8)(9)(10)(11)(12)(13)(14). The cohort study that examined the risk of ALS in people with MS, found that MG and polymyositis were also associated with later ALS risk (4).…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…The concurrence between ALS and MG has also been reported (3,(7)(8)(9)(10)(11)(12)(13)(14). The cohort study that examined the risk of ALS in people with MS, found that MG and polymyositis were also associated with later ALS risk (4).…”
Section: Introductionmentioning
confidence: 81%
“…The association of dermatomyositis and polymyositis with ALS was later confirmed in other populations (3,15). In contrast, the overlap between ALS and IP such as Guillain-Barr e syndrome (GBS) has been reported only in the Swedish population (3).…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations